La lingua in servizio alla persuasione - Pastucha-Blin, Agnieszka (Neophilologica, 2013)
These considerations are developed within the cognitive approach to language study. They represent an attempt to discuss the mechanisms of language used by writers to achieve a persuasive impact on the recipient (by inducing emotion, influencing the recipient’s consciousness, imagination and reactions). The article characterizes linguistic actions which are intended to influence the decisions of customers by imposing a particular vision of reality on them. Undoubtedly, the use of appropriate lexemes (borrowings, technical vocabulary) and syntactic structures (causal structures between compound sentences, subordinate conditionals) belongs to this type of strategy.